2006
DOI: 10.4049/jimmunol.176.1.248
|View full text |Cite
|
Sign up to set email alerts
|

Virus or TLR Agonists Induce TRAIL-Mediated Cytotoxic Activity of Plasmacytoid Dendritic Cells

Abstract: Among dendritic cells, plasmacytoid dendritic cells (PDC) represent a functionally distinct lineage. Regarding innate immunity, PDC secrete large amounts of type I IFN upon viral exposure or stimulation by microbial products such as unmethylated CpG-motif containing oligo-DNA due to their selective expression of TLR7 and TLR9. We asked whether they could acquire cytotoxic functions during the early phases of infection or after activation with TLR7 or TLR9 agonists. In the present study, we describe a human PDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
270
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(281 citation statements)
references
References 53 publications
(57 reference statements)
8
270
1
2
Order By: Relevance
“…TRAIL induces apoptosis of a variety of tumor cells while displaying no cytotoxicity against most normal cells; this makes it a promising new agent for cancer therapy. It has been reported that in immune cells, TRAIL is induced mainly by the type I or II IFN-mediated JAK/STAT (37)(38)(39)(40) and TLR agonist-mediated TLR pathways (41)(42)(43). To our knowledge, this is the first report that TRAIL expression is mediated by integrin aM, and our findings should add to understanding of the mechanisms regulating TRAIL expression.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…TRAIL induces apoptosis of a variety of tumor cells while displaying no cytotoxicity against most normal cells; this makes it a promising new agent for cancer therapy. It has been reported that in immune cells, TRAIL is induced mainly by the type I or II IFN-mediated JAK/STAT (37)(38)(39)(40) and TLR agonist-mediated TLR pathways (41)(42)(43). To our knowledge, this is the first report that TRAIL expression is mediated by integrin aM, and our findings should add to understanding of the mechanisms regulating TRAIL expression.…”
Section: Discussionmentioning
confidence: 76%
“…It is expressed on activated T cells, NK cells, macrophages, monocytes, dendritic cells, and neutrophils and plays important roles in tumor surveillance and defense against viral infections and many other physiological and pathological processes (35,36). In immune cells, TRAIL is induced by several pathways including the type I or II IFN-mediated JAK/STAT (37)(38)(39)(40) and TLR agonist-mediated TLR pathways (41)(42)(43). Histone deacetylase inhibitors induce TRAIL in human breast tumors via the transcription factor Sp1 (44), and proline oxidase promotes TRAIL expression via NFAT (45).…”
mentioning
confidence: 99%
“…In one case, DNA was obtained from a CD4+ CD56+ cell line (GEN2.2). 10 In the interests of clarity, the GEN2.2 line is referred to as case 1 throughout the manuscript.…”
Section: Patient Selection and Materialsmentioning
confidence: 99%
“…Finally, inflammatory chemokines can attract activated T cells to sites of inflammation [20]. Interestingly, it has been shown that PDCs can induce apoptosis of tumour and virus-infected cell lines, either directly by secreting TRAIL (TNF-related apoptosis-inducing ligand) upon activation, or indirectly via the effect of type I IFN on other cytotoxic cells [24,25]. PDCs contain abundant granzyme B, but the role of this enzyme as a cytotoxic molecule remains elusive, because PDCs, in contrast to other cytotoxic cells, lack the pore-forming perforin [1,26].…”
Section: Background On Pdcs: History and Functionmentioning
confidence: 99%